Metacognitive Awareness of Strategy Use in EFL Reading Comprehension in Bangladesh - Tasnima Aktar; Ilias Ahmed (Journal of ELT Research, 2018)
It is argued that learners’ metacognitive awareness of strategy use is significantly associated with their achievement in reading comprehension. In order to ascertain this association, the present researcher carries out the investigation to substantiate the existing findings. This current study is a partial replication of Carrell (1989) and Vogely (1995) with regard to their methods and objectives. The objectives of this research are to explore the higher secondary-level EFL learners’ perceptions of themselves as readers, of their use of comprehension and repair strategies, of difficulties as well as the effectiveness of reading strategies, and its relationship with their reading comprehension, if any. For this investigation, quantitative data collected from 148 higher secondary-level EFL learners via a modified Metacognitive Awareness Strategy Questionnaire (MASQ; Carrell, 1989) and a reading comprehension test were analyzed through statistical tools available in SPSS. The results reveal that learners possess a moderate awareness of reading strategies, and their perceptions of effective strategies and of the difficulty of strategy use are significantly and positively related to their reading comprehension. Based on the findings, pedagogical implications are discussed and scope for future studies is recommended.